Problem-Based Learning Interactive Learning Multimedia to Improve Science Content Learning Competency - Adrianus I Wayan Ilia Yuda Sukmana; Akmal; I Kadek Suartama (Universitas Pendidikan Ganesha, 2023)
The lack of instructional media relevant to student characteristics results in a low quality of science content learning. This study aims to develop problem-based learning interactive multimedia to improve students' competence in science content. This research is development research using the ADDIE model. The subjects involved in this study were one learning content expert, one instructional design expert, one instructional media expert, and sixth-grade students. Data collection in the study was carried out using questionnaires and tests (pretest and post-test). The data obtained in the study were then analyzed using descriptive qualitative, quantitative, and inferential statistical analysis techniques. The results showed that the product was valid in terms of the aspect of learning content 97% (very good); learning design aspect 96% (very good); learning media aspect 91% (very good); individual trial aspect 96.66% (very good); small group trial aspect 94.77% (very good); aspect of field trials 94.35% (very good). Based on the effectiveness results, interactive multimedia based on problem-based learning in science content subjects showed significant differences in student learning outcomes before and after using interactive multimedia. It shows that problem-based learning-based interactive multimedia in science content subjects are declared feasible for use in the learning process.